Effect of Temperature on the Germination and Spread of the Mycelia of Sporisorium scitamineum Fungus Causes Smut Disease in Sugarcane - Tasya, Tasya; Muhibuddin, Anton; Sektiono, Antok Wahyu; Hidayah, Nurul (Research Journal of Life Science, 2024)
Sugarcane is presumed to be susceptible to smut disease caused by a basidiomycete fungus, Sporisorium scitamineum. One environmental condition that influences the disease's development is temperature. However, information related to smut disease, especially the influence of the environment (temperature) on the growth of S. scitamineum in sugarcane, is limited. Therefore, studying the effect of different temperature ranges on S. scitamineum growth is necessary. The research, which was arranged using a completely randomized design with 3 (replicates) consisted of two treatments, including temperatures (20, 25, 30, and 35°C) and incubation time (1, 2, 4, and 6 hours). The teliospore suspension was inoculated on a water agar medium and incubated at different times and temperatures. After each allocated time, the plates were taken from the incubator, and then germination of teliospores was observed under a compound microscope. In addition, we also conducted research on the effect of inoculation temperature (25, 30, and 35°C) on the mycelial distribution within sugarcane tissue. The bud setts were immersed in teliospore suspension for 10 minutes at different temperatures, then planted in the polybags and kept for one and two weeks. The results showed that temperature affected the germination of S. scitamineum teliospores, in which the highest germination (92,3%) occurred at 30°C. On the other hand, the lowest germination was at 20°C with 0% germination after 1 hour incubation time. The in vivo study revealed that the distribution of mycelia within sugarcane tissue was similar, either incubated in one or two weeks.